Pengaruh Kualitas Pelayanan terhadap Kepuasan Masyarakat pada Kantor Kelurahan Sobo Kecamatan Banyuwangi Kabupaten Banyuwangi - Widuri, Ayu; Ginting, Aditya Madinta Putra; Harsono, Moh.; Qomariah, Nurul; Nursaid, Nursaid (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Providing service to customers is a strategy to win the competition. With increasing business competition, every service provider must be able to provide the best service so that customers get satisfaction. This research aims to analyze the impact of the services provided on community satisfaction in Sobo Banyuwangi Village. All people who have an interest in the Sobo Banyuwangi Subdistrict Office are used as the population in this research. The number of samples was determined as 40 (forty) people using a minimum sample determination method of 5 to 10 multiplied by the number of indicators. Descriptive analysis to find out about respondents related to gender, age and education. The measuring instrument used will be tested for its level of validity and reliability. To answer the hypothesis developed using multiple linear regression. To determine the contribution of the independent variable to the dependent variable, analysis of the coefficient of determination (R2) is used. The calculation results show that the quality of services provided by the Sobo Banyuwangi Subdistrict Office has an impact on community satisfaction. The contribution of the service quality variable is 63.9%. Keywords: Community Satisfaction, Service Quality, Sobo Village Office.